Trends, Gaps, and Collaboration in Facial Transplantation: A Bibliometric Study - Alexandra F. Hoffman, BS (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Facial transplantation (FT) has advanced extensively over the past two decades, with over 40 transplants performed to date. Over this time, the FT literature has evolved as well, from early discussions on ethics and feasibility of FT to functional outcomes reports more recently. We aimed to evaluate the entire body of FT literature to identify trends in publications over time in addition to current existing gaps in the field. Methods:. We conducted a comprehensive bibliometric analysis of the published FT literature from 1994, the first year FT was mentioned in the literature, through July 2020. Co-authorship and keyword information were analyzed using VOSviewer. Articles were manually categorized based on keywords and their aim to provide insight on trends. Results:. A total of 2182 articles were identified. Analysis identified the top 50 publishing authors in the field and demonstrated co-authorship linkage between 84.8% of the top 1000 authors. Clinical surgical techniques, protocols, and experiments were the most frequently published category. Within clinical outcomes, immunologic outcomes were most frequent, while psychosocial were the lowest. Gaps were identified in long-term outcomes reporting and patient-reported outcomes, with physician-reported outcomes heavily outweighing patient-reported outcomes. Conclusions:. As the field continues to evolve, rigorous tracking of publication patterns over time will encourage development of a more robust evidence base, identify gaps in the published literature, and highlight opportunities to enhance collaboration in the field. This data will provide surgeons and research institutions with information to further improve this life-changing procedure.